The Effectiveness of Copyright Law in Addressing Digital Copyright Infringement in the Musical Industry of Uganda - Joan Tusiime (Uganda Christain University, 2024)
This research focuses on assessing the relevance of copyright law to Ugandan musicians and the provisions of the Copyright and Neighbouring Rights Act, 2006 that protect music copyright. The research also discusses the problems encountered by music copyright owners in enforcing their rights. The emphasis of this research is based on the fact that very few musicians benefit from their musical works and this seems to be attributed to the rapid digital transformation that have made music infringement easy. The conclusions reached in this research is that copyright laws alone cannot combat music infringement and that different enforcement bodies and institution should join in to fight music piracy.